Let g the inverse function of f.
The most important property of g and f being inverses of each other, is that
g(f(x))=x, also f(g(x))=x
so, what one function 'does' to x, the other 'undoes' it.
Thus, we have:
f(g(x))=x and alos f(g(x))= -g(x)+3, from the rule
thus :
-g(x)+3=x
-g(x)=x-3
g(x)=-x+3
check: f(g(x))=f(-x+3)=-(-x+3)+3=x-3+3=x
Answer: the inverse of f is g, such that g(x)=-x+3
Answer:
x = 14
Step-by-step explanation:
The polygon given has 6 sides
Sum of interior angles of a 6-sided polygon = 180(n - 2)
substitute n = 6 into 180(n - 2)
Sum of the polygon = 180(6 - 2) = 720°
Thus:
10x + 8x - 16 + 12x - 8 + 7x + 2 + 9x + 4 + 6x + 10 = 720
Add like terms
52x - 8 = 720
52x = 720 + 8
52x = 728
x = 728/52
x = 14
Answer:
1080cm²
Step-by-step explanation:
surface area=sum of the area of all the shapes
area of triangle=1/2*base*height
1/2*24*10=120*2(because there are two triangles)=240cm²
10*14=140cm²
24*14=336cm²
Area of slanting figure=26*14=364cm²
add all the results
240+140+336+364=1080cm²
Answer:1 7/8
Step-by-step explanation: 5 multiplied by 3 is 15 and 15/8 and since 8 goes into 15 once with 7 left over, the answer is 1 and 7/8
Answer: Length = l
Width = w
2l + 2w = 80cm
l+w = 40cm
l = w+4
w+4 + w = 40cm
2w + 4 = 40cm
2w = 36cm
w = 18cm
l = 22cm
jd3sp4o0
Step-by-step explanation: